2018
DOI: 10.1039/c7ay02406a
|View full text |Cite
|
Sign up to set email alerts
|

A new solidified effervescent tablet-assisted dispersive liquid–liquid microextraction for the analysis of fungicides in fruit juice samples

Abstract: A simple and rapid pretreatment method based on effervescent tablet-assisted dispersive liquid–liquid microextraction was introduced for the determination of three fungicides (azoxystrobin, chlorothalonil, and cyprodinil) in fruit juice samples followed by liquid chromatography–ultraviolet detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The results indicated that citric acid and Na 2 CO 3 as an effervescence pair provided the highest extraction recovery for methadone. Regarding the effervescent time, bicarbonate has shorter effervescence time which may decrease the extraction recovery due to lower contact time between the extraction solvent and the ana-lyte [35]. Moreover, bicarbonate has lower thermal stability than carbonate [35].…”
Section: The Composition and Amount Of Effervescent Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that citric acid and Na 2 CO 3 as an effervescence pair provided the highest extraction recovery for methadone. Regarding the effervescent time, bicarbonate has shorter effervescence time which may decrease the extraction recovery due to lower contact time between the extraction solvent and the ana-lyte [35]. Moreover, bicarbonate has lower thermal stability than carbonate [35].…”
Section: The Composition and Amount Of Effervescent Agentsmentioning
confidence: 99%
“…Regarding the effervescent time, bicarbonate has shorter effervescence time which may decrease the extraction recovery due to lower contact time between the extraction solvent and the ana-lyte [35]. Moreover, bicarbonate has lower thermal stability than carbonate [35]. Therefore, the combination of citric acid and Na 2 CO 3 showed a longer effervescent reaction time compared to other sources because of the smooth release of the hydrogen ions and more persistent effervescent reaction.…”
Section: The Composition and Amount Of Effervescent Agentsmentioning
confidence: 99%
“…Yıldız and Çabuk proposed a tablet based on a tertiary mixture containing Na 2 CO 3, NaH 2 PO 4 and 1-dodecanol [ 44 ] for the extraction of fungicides from fruit juice. For the fabrication, all the ingredients were manually blended and cooled in a refrigerator to produce the solidification of the 1-dodecanol increasing the consistency of the tablet.…”
Section: Effervescence-assisted Dispersive Liquid-phase Microextramentioning
confidence: 99%
“…Dispersion techniques are commonly accelerated using manual shaking, magnetic stirring, air, vortex, surfactant emulsion, ultrasound, microwave, or effervescent tablets (Leong et al, 2014). An effervescent tablet is a soluble tablet that involves acid-base reaction that produces carbon dioxide (CO2) bubbles, thus making it possible for fine dispersion of extraction solvent in an aqueous sample (Yıldız & Çabuk 2018). This method is very rapid, effective, and reliable.…”
Section: Introductionmentioning
confidence: 99%